Pemberdayaan Masyarakat di Kawasan Menoreh Desa Pagerharjo dan Sekitarnya dalam Penggunaan Smartphone Berbasis Android - Rella Mareta; Fitri Puspa Sari (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
Kulon Progo Regency is one of the districts in Yogyakarta Special Region which has great potential, especially its tourism potential. Pagerharjo village located in District Samigaluh, which is part of the Menoreh region, is an area that has a lot of tourism potential and local products. But this great potential has not been widely known by the public. Advances in technology such as android-based smartphones are widely known as one of the popular online media used for promotion. However, the utilization of this android-based smartphone as a medium of potential promotion of the region has not been so maximized, especially in the Pagerharjo and its surrounding areas. Therefore, the Department of Electrical and Informatics Engineering, Vocational School of Gadjah Mada University conducted the Training of Android Smartphone. The training was conducted with participants from Pagerharjo Village's Youth and Housewife Organization.